Performance of various TaqMan and SYBR Green rRT-PCR methods in detecting the Egyptian foot-and-mouth disease viruses (Global Journal of Medical Research, 2018)
Proficient application of the advanced technology for foot-and-mouth disease virus (FMDV) detection, still a target challenge in Egypt, not only for rapid, identification of the transboundary continuously evolving virus, but also support accurate control strategy involving manufacturing of a highquality protective vaccine. The article discussed both two real-time RT-PCR (rRT-PCR) methods depending on either fluorophore or fluorescent dye for the precise detection of FMDV few copies. TaqMan based probe/primer overcame SYBR Green-based primer rRT-PCR by 10-fold for detecting less FMDV nucleic acid. In contrary, lower threshold cycles values with fewer nucleic acid copies biased to the fluorescent RRT-PCR with 3-4 cycles earlier. TaqMan format had better sensitivity and specificity, while SYBR Green method displayed less detection limit and precision.
Keywords: foot-and-mouth disease virus; rRT-PCR; taqman